Perceived value in the online shopping environment:|The case of supermarket shopping - Karabağ, Seçkin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Online retail sales grow faster than total retail sales every year. It is not only because of increasing internet penetration but also due to product diversification. Supermarket shopping has also been transformed to an online experience by many brands today. This study aims to measure the importance of perceived value and behavioral perception on online supermarket shopping intention and purchase decision. The theoretical framework and hypotheses are based on the perceived online channel value (POCVAL) model. The original model is extended with SERVQUAL, experiential value and behavioral perception scales in order to detail the effects of service performance, emotional value, perceived capability and social encouragement factors. Data collected from 458 respondents are analyzed on SPSS using descriptive, multiple and logistic regression, mediation, one-way ANOVA and independent sample t-test analyses. Results show that behavioral perception factors have both significant direct and indirect impacts on online supermarket shopping intention. Beside that personalized features and information quality from service performance values have positive or negative impacts on both intention and actual purchase decision. Furthermore, without social encouragement both enjoyment and visual aesthetics of online supermarkets become futile, which implies that word-of mouth effect is strongly needed for online supermarkets as well. Nevertheless, this study reflects only the perspective of Turkish consumers. Validation of the applied model in other cultural settings is needed. Moreover, hands-on experiments and focus groups are needed for further research to explore more of purchase triggers.
Keywords: Mobile commerce.; Grocery shopping.